Gamma Radiation-Induced Effects over an Optical Fiber Laser: Towards New Sensing Applications † - Perez-Herrera, Rosa Ana (Sensors (Basel), 2020)
In the present work, the effect of gamma radiation on the performance of different types of erbium-doped fibers (EDFs) when they are used in a fiber ring cavity (FRC) configuration is studied. Several pieces of commercial EDF are gamma-ray irradiated with different doses to evaluate the output power variations over time. The influence of different doses, from 150 Gy to 1000 Gy, over the output power level measurement and their amplified spontaneous emission (ASE) are experimentally evaluated both in the C and L bands. By using an FRC configuration we can detect the presence of gamma radiation. We can also estimate the irradiation doses applied to EDFs by measuring the slope of the short-term emission power.